Elastoplastic Finite Element Analysis of Masonry Shear Walls - Koksal, H. Orhun; Doran, Bilge; Kuruscu, A. Osman; Kocak, Ali (KOREAN SOCIETY OF CIVIL ENGINEERS-KSCE, 2016)
Masonry is the most important construction material in Turkey. It has been used for public and residential buildings in the past several thousand years. A great number of well-preserved old masonry structures still exist proving that this form of construction can successfully resist loads and environmental impact. Traditionally, most major buildings were solid walled structures with the walls bearing directly on the ground. Engineers work hard to convert the highly indeterminate, ambiguous and nonlinear behavior of historic masonry construction into something which can be understood with mathematical certainty. Therefore, practical and accurate structural analysis techniques are needed for the preserve the historical monuments as a huge cultural heritage. This paper is focused on Nonlinear Finite Element (NLFE) modeling of masonry shear walls at a macro-level taking the geometric arrangement of constituents. In this study, 3D elasto-plastic Finite Element (FE) analysis for the masonry walls that subjected to the combinations of vertical and lateral loads, are determined to find a practical method. An original meshing procedure is introduced to consider the orthotropy along the two natural directions of the masonry while the material is still assumed to be isotropic. The paper further examines parameter studies carried out to show that the relation suggested for cohesion values of mortar joint masonry can also be adopted for the masonry walls with dry joints employing compressive stresses on the top surface of the wall despite using its compressive strength. The accuracy of the proposed approach is verified by simulating a series of experiments reported in the literature. Those papers include shear tests on masonry walls with both dry and mortar joints by Raijmakers and Vermeltfoort, Oliveira and Roca. Comparisons between the predicted and measured failure loads of the walls confirm that it is possible to reproduce the fundamental features of masonry shear walls with the proposed meshing scheme. Finally, the proposed approach is shown to fit quite well the experimental load-deformation plots of masonry walls with both dry-and mortar joint under shear-compression fracture.
Keywords: masonry wall; finite element analysis; plasticity; load-displacement curves; Drucker-Prager criterion; NONLINEAR-ANALYSIS; MODEL; BUILDINGS; COLUMNS; PERIOD; Engineering